Trends in socioeconomic inequality in mortality during childhood between 1993 and 2021 in India - Soumya Swaminathan; Rockli Kim; S V Subramanian; Anoop Jain; Akhil Kumar; Thomas W Pullum (BMJ Global Health)
Introduction In India, most child deaths now occur within the first 28 days of birth. Trends in socioeconomic disparities in death during these early and late neonatal stages over the past few decades have been understudied. This paper elucidates these trends in early neonatal and late neonatal mortality by household wealth and maternal education. We also examined these trends for post neonatal and child mortality, thereby examining the risk of death by socioeconomic status from birth until 59 months.Methods Using data from five rounds of India’s National Family Health Survey, we examined how the early neonatal, late neonatal, post neonatal and child mortality rates changed between 1993 and 2021 by household wealth and maternal education. We also examined how the absolute (difference in rates) and relative (ratio of rates) inequality between the highest and lowest socioeconomic groups changed for each outcome, and which children are on track to meet the Sustainable Development Goal targets.Results Despite large absolute reductions in early neonatal, late neonatal, post neonatal and child mortality, India’s most vulnerable children remain at the highest risk of death as of 2021. Between 1993 and 2021, the absolute and relative socioeconomic inequality for early neonatal deaths increased. Now, most child deaths are among India’s most vulnerable children in terms of household wealth and maternal education, and these children are not on track to meet the Sustainable Development Goal targets for early neonatal and post neonatal mortality.Conclusions Our study highlights persistent socioeconomic inequalities in child death, and that these inequalities exist regardless of mortality stage. More pro poor policies and interventions are required to close these gaps. Doing so is essential for India to meet global targets.